Complicance with single-dose diethylcarbamazine citrate (DEC) mass treatment programme for filariasis in Colombo, Sri Lanka - Weerasinghe, C.R.; Abeyewickreme, W.; de Silva, N.R. (World Health Organization Regional Office for South-East Asia, 2002)
Available
Keywords: Filariasis